The Water of the Living: An Assessment of the Microbiological Elements in Catholic Churches Across Quezon City - Castaneda, Nico Angelo; Colleges, World Citi (International Journal of Psychosocial Rehabilitation, 2020)
Majority of Filipinos are Catholic devotees. Thus, it is part of Catholic custom that a devotee, upon entering the holy place, should dip their forefingers in the holy water font posted within the entrance of the sanctum and make the sign of the cross. However, this customary practice has its implications in public health. Recently, a landmark study by Kirschner et al. (2012) reported contaminations of holy water fonts and holy springs in Vienna, Austria, with cell counts of up to 107 colony forming units (CFU) ml−1, and the presence of fecal indicator bacteria such as enterococci and E. coli. The researcher aims to provide an assessment of the conditions of holy water fonts by testing Catholic Churches within Quezon City for the presence of microorganisms with the aim to provide public health awareness to church goers as well as make recommendations on how to limit infections from a potential microbiologic reservoir.